Spinal Cord Injury Creates Unique Challenges in Diagnosis and Management of Catheter-Associated Urinary Tract Infection - Skelton-Dudley, Felicia (Top Spinal Cord Inj Rehabil, 2019)
Background: Catheter-associated urinary tract infection (CAUTI) is associated with increased morbidity and mortality and influences the quality of life of patients with spinal cord injury (SCI). Objectives: This clinical review aims to highlight the unique surveillance, prevention, diagnosis, and management challenges of CAUTI in the SCI population. Methods: Narrative review of the current literature on catheter use in persons with SCI was conducted to determine gaps in knowledge and opportunities for improvement. Results: Surveillance of CAUTI is challenging in the SCI population as the ability to detect symptoms used to diagnose CAUTI (ie, suprapubic pain, dysuria) is impaired. In terms of prevention of CAUTI, current strategies refocus on appropriate catheter insertion and care and early removal of catheters, which is not always feasible for persons with SCI. Prophylactic antibiotics, nutraceuticals, and coated catheters show limited efficacy in infection prevention. Diagnosing CAUTI after SCI is challenging, often resulting in an overdiagnosis of CAUTI when truly asymptomatic bacteriuria exists. In the management of CAUTI in patients with SCI, the use of multiple antibiotics over time in an individual increases the rate of multidrug-resistant organisms; therefore, the exploration of novel non-antibiotic treatments is of importance. The patient experience should be at the center of all these efforts. Conclusion: Better diagnostic tools or biomarkers are needed to define true CAUTI in people with SCI. SCI-specific evidence to inform catheter management and CAUTI treatment guidelines is needed, with the goal to minimize catheter-related harm, reduce antibiotic resistance, and improve satisfaction and overall quality of life for SCI patients.